MBA ITB Competitive Advantages Enhancement Proposal to Face Global Business School Competition ( Benchmarking Study of South East Asia Business School) (The Indonesian Journal of Business Administration, 2012)
The competition in the higher education industry continues to grow, both from the scope of science, universities, and programs are offered. Higher education inbusiness and management field in Indonesia from year to year is growing in demand.External factors such as the condition of the business world that change dynamically should become special interest to business school, MBA ITB in this case because it will greatly affect the supply of programs and courses offerings to the students. Internal factors such as improving the quality of the various supporting elements of the course, ranging from facilities, curriculum, quality of lecturer, and administrative staff should be a serious attention from MBA ITB.To increase competitive advantages of MBA ITB to be able to compete with their competitors, the researcher does benchmarking in programs and lecturing methods from abroad university and from ASEAN country specifically. The solution from this research is recommendation for MBA ITB in regular programs, such as Soft Skill, Management, and Strategy, Economy, and Information Technology. Besides that, there is also recommendation of elective program. In lecturing methods, the researcher recommends to use On Job Training and Virtual Project more actively, as addition for Case Study methods. To reach world class business school MBA ITB needs to encourage their student to write international publication based on their final project as pre-requisites for final defence. Keywords: Sustainability, Curriculum, Graduate Program, Benchmarking, Business School